Characterization of a Human Respiratory Mucosa Model to Study Odorant Metabolism - Mérignac-Lacombe, Jeanne; Kornbausch, Nicole; Sivarajan, Rinu; Boichot, Valentin; Berg, Kevin; Oberwinkler, Heike; Saliba, Antoine Emmanuel; Loos, Helene; Ehret Kasemo, Totta; Scherzad, Agmal; Bodem, Jochen; Büttner, Andrea; et al. (Journal of agricultural and food chemistry, 2024)
Nasal xenobiotic metabolizing enzymes (XMEs) are important for the sense of smell because they influence odorant availability and quality. Since the major part of the human nasal cavity is lined by a respiratory mucosa, we hypothesized that this tissue contributed to nasal odorant metabolism through XME activity. Thus, we built human respiratory tissue models and characterized the XME profiles using single-cell RNA sequencing. We focused on the XMEs dicarbonyl and l-xylulose reductase, aldehyde dehydrogenase (ALDH) 1A1, and ALDH3A1, which play a role in food odorant metabolism. We demonstrated protein abundance and localization in the tissue models and showed the metabolic activity of the corresponding enzyme families by exposing the models to the odorants 3,4-hexandione and benzaldehyde. Using gas chromatography coupled with mass spectrometry, we observed, for example, a significantly higher formation of the corresponding metabolites 4-hydroxy-3-hexanone (39.03 ± 1.5%, p = 0.0022), benzyl alcohol (10.05 ± 0.88%, p = 0.0008), and benzoic acid (8.49 ± 0.57%, p = 0.0004) in odorant-treated tissue models compared to untreated controls (0 ± 0, 0.12 ± 0.12, and 0.18 ± 0.18%, respectively). This is the first study that reveals the XME profile of tissue-engineered human respiratory mucosa models and demonstrates their suitability to study nasal odorant metabolism.
CRIS-Team Scopus Importer:2024-05-31
Keywords: human respiratory tissue models; nasal odorant metabolism; perireceptor events; tissue engineering; xenobiotic metabolizing enzymes

Geruchsstoffmetabolismus im Menschen - Kornbausch, Nicole; Debong, Marcel; Büttner, Andrea; Heydel, Jean-Marie; Loos, Helene (Angewandte Chemie, 2022)
Geruchsstoffe sind verhältnismäßig kleine Moleküle, welche vom menschlichen Körper leicht aufgenommen werden können. Trotz ihrer großen Relevanz im Alltag ist vergleichsweise wenig über ihren Metabolismus, ihre Verteilungswege und ihre Bioaktivität im menschlichen Körper bekannt. Mit diesem Aufsatz möchten wir zu interdisziplinärer Forschung an den Schnittstellen zwischen Ernährungswissenschaften, Medizin, Biochemie, Chemie und Wahrnehmungswissenschaften beitragen, um das Wissen über die Mechanismen und Funktion der Biotransformation von Geruchsstoffen zu erweitern. Innerhalb des Artikels wird zunächst ein allgemeiner Überblick über die Aufnahme von Geruchsstoffen und die bei der Verstoffwechselung beteiligten Enzyme gegeben. Anschließend wird speziell auf die Biotransformation im Mund- und Nasenraum sowie in der Lunge und im Gastrointestinaltrakt eingegangen, und die verschiedenen Ausscheidungswege werden aufgezeigt. Schließlich wird ein Ausblick auf die zukünftige Forschung gegeben und diskutiert.<br

Odorant Metabolism in Humans - Kornbausch, Nicole; Debong, Marcel; Büttner, Andrea; Heydel, Jean-Marie; Loos, Helene (Angewandte Chemie International Edition, 2022)
Odorants are relatively small molecules which are easily taken up and distributed in the human body. Despite their relevance in everyday life, however, only a limited amount of evidence about their metabolism, pathways, and bioactivities in the human body exists. With this Review, we aim to encourage future interdisciplinary research on the function and mechanisms of the biotransformation of odorants, involving different disciplines such as nutrition, medicine, biochemistry, chemistry, and sensory sciences. Starting with a general overview of the different ways of odorant uptake and enzymes involved in the metabolism of odorants, a more precise description of biotransformation processes and their function in the oral cavity, the nose, the lower respiratory tract (LRT), and the gastrointestinal tract (GIT) is given together with an overview of the different routes of odorant excretion. Finally, perspectives for future research are discussed.
CRIS-Team WoS Importer:2022-08-26

Perspectives on Nasal Odorant Metabolism Research - Kornbausch, Nicole; Mérignac-Lacombe, Jeanne; Neiers, Fabrice; Thomas-Danguin, Thierry; Heydel, Jean Marie; Steinke, Maria; Hackenberg, Stephan; Loos, Helene (Journal of agricultural and food chemistry, 2023)
Olfaction is a multi-step process. At a peripheral level, nasal odorant metabolism contributes to olfaction via signal termination, variation, and regulation. We summarize current techniques used to investigate nasal odorant metabolism and give an outlook on future approaches, such as nasal tissue models and their potential contributions in future research directions.
CRIS-Team Scopus Importer:2023-11-24
Keywords: aroma perception; enzymes; gas chromatography−mass spectrometry; metabolites; proton transfer reaction−mass spectrometry; regulation; tissue engineering